Elements of the characteristics of the principles of individual freedom - Загоруй, Людмила Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article formulated a number of scientific and reasonable provisions aimed at in-depth understanding of freedom of individual civil right. Discussions on the definition of the signs and principles of civil law, classification criteria and search systemforming basis, problems elemental composition of sectoral problems in the implementation of rule-making and in the implementation of justice in civil cases continue in legal literature. The issue about the nature of the principles of civil law, including the principle of individual freedom is equally important. The question of the nature of the principles of civil law in civil law was considered by leading Soviet and modern scientists. Based on the analysis of legal literature we concluded that traditional legal nature of the principles studied in the plane of the definition of "principles". This category is characterized from different sides. We stand in solidarity with specified scientists. But consider that the question of the nature of the principles of civil law should be considered more broadly, and also explore the elements of characteristics. With these in mind the principle of freedom of an individual is considered as having genetic, epistemological, ontological and functional characteristics. Conceptual formulation of the principle of freedom of individual civil right can argue using objective and subjective in the principles. Such a mechanism of interaction was justified G. Sverdlik. Using some of his results on this issue, we noted that the subjective is in that legal principles are the result of conscious activity (people, groups and society in common). The objective, however, is that positions expressed by principles do not depend on whether they are known, understood, guided by subjects of civil law during their activities or not. Objective reality is also reflected in their commitment, as all actors of civil law, and for the legislator. In view of above we separate objective characteristics that, in our view, affect the formation of freedom of individual civil right. Conventionally, they named the genetic, epistemological, ontological, and functional characteristics. From this perspective the said principle is not investigated, which determines the relevance of this issue. In the genetic aspect the principle of individual freedom is characterized by mixed social and legal nature. In the epistemological aspect it is characterized by specific legal structure that expresses the essence of modern civil law. From the ontological point of view the principle of freedom an individual has different forms of existence - in law, in legal system, in science, in the legal consciousness. In the functional aspects the researched principle performs internal and external functions in civil law. Thus, understanding the nature of the principle of the elements of its characteristics - is the working tools, which will contribute to the development of understanding of the civil law and is the basis for further substantial reform of civil law.